DAMPAK PEMAHAMAN FLIGHT OPERATION OFFICER MENGENAI FLIGHTPLAN TERHADAP PELAYANAN ARO DI PERUM LPPNPI CABANG MATSC - Achmad Adhitya Pratama; Laila Rochmawati; Arnaz Olieve (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final project describes the obstacles faced by the author regarding the impact of understanding the ATS Message from a FOO personnel on the provision of services from the ATS-RO with the units related to the delivery of ATS Message news at Perum LPPNPI MATSC Branch. There are still many personnel from an airlanes, especially FOO who still do not fully understand the contents or provisions contained in the flight plan which results in the ineffectiveness of the ATS Message news delivery process in the ATS-RO unit so that this has an impact on traffic flow obstruction. flight. The emergence of these obstacles is due to the frequent delays of the Airline in sending information regarding changes to the time slot on the new ATS Message via the Web Flight Plan (WBF) so that the process of sending ATS Message news by ATS-RO personnel on duty will be hampered, in addition to the delay in providing information on news changes. The ATS Message often causes the ATS-RO to be subject to complaints from the ATC regarding "why the plane that is about to fly but does not have a flight plan and the ATC questions whether this aircraft can be given a flight permit or not", and therefore has an impact on adding The workload of ATS-RO personnel, according to the author's analysis, is not in accordance with the existing LOCA. The purpose of writing this final project is to find out the impact that occurs regarding the understanding of ATS Message FOO on the provision of ATS-RO services to related units. The method used is descriptive qualitative to describe the conditions and facts that occur based on data obtained by conducting observations, questionnaires and interviews that have been conducted for five months on November 2, 2020 - March 31, 2021. This study uses data processing in the form of a Likert scale. which refers to sources that are relevant and have credibility. The results of this study are expected to provide alternative problem solving so that ATS-RO personnel can provide maximum service.